An Assessment Study of the National Archives and Records Management System (NARMS) at Botswana National Archives and Records Services (BNARS) - Motlhasedi, Nna (Mousaion: South African Journal of Information Studies, 2025)
The purpose of this study was to explore the National Archives and Records Management System (NARMS) at Botswana National Archives and Records Services (BNARS). The study specifically sought to explore metadata management practices and evaluate the infrastructure for digital records keeping. The study adopted a qualitative research design and used a purposive sampling technique to select study respondents. For data collection, the study adopted the use of a self-administered questionnaire, scheduled interviews and document analysis, whereas, for data analysis, the study employed a thematic analysis approach. The study’s major finding is that metadata management is done manually by designated officers (records managers and archivists). It is, therefore, recommended that BNARS consider transformation that would automate some aspects of specifically born-digital records’ metadata to improve and sustain reliable metadata and the authenticity of records.